2020
DOI: 10.1055/a-1301-7011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an 8-week Exercise Training on Gut Microbiota in Physically Inactive Older Women

Abstract: Exercise can alter the composition of gut microbiota. However, studies examining the effects of exercise on gut microbiota in the elderly are lacking. This study aims to investigate whether an 8-week exercise training affect gut microbiota in physically inactive elderly women. Fourteen women were randomly assigned to either exercise group or control group. Repeated-measures analysis of variance was used to reveal changes in gut microbiota. Alpha diversity did not change significantly. A tendency to form 2 clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 60 publications
2
69
0
Order By: Relevance
“…Previous studies have shown that PA/exercise have several benefits during the ageing process such as improvements in cognitive function [ 55 , 56 ], promotion of cardiovascular health [ 57 ] and improvements in the musculoskeletal system [ 58 , 59 , 60 ], making it a precious tool to counteract the age-associated changes that occur in those systems. Besides the benefits mentioned previously, recent studies [ 61 , 62 , 63 , 64 ] on the effects of exercise on the gut microbiome of older people have suggested that exercise might beneficially affect its composition and even reverse some age-associated taxonomical changes, ultimately leading towards healthy ageing. This is a relatively new topic of research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that PA/exercise have several benefits during the ageing process such as improvements in cognitive function [ 55 , 56 ], promotion of cardiovascular health [ 57 ] and improvements in the musculoskeletal system [ 58 , 59 , 60 ], making it a precious tool to counteract the age-associated changes that occur in those systems. Besides the benefits mentioned previously, recent studies [ 61 , 62 , 63 , 64 ] on the effects of exercise on the gut microbiome of older people have suggested that exercise might beneficially affect its composition and even reverse some age-associated taxonomical changes, ultimately leading towards healthy ageing. This is a relatively new topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…This is a relatively new topic of research. As such, human intervention studies are limited and there are only a few observational studies that have assessed this research question [ 61 , 63 , 64 , 65 , 66 , 67 , 68 ]. This systematic review aims to summarise results of human studies that assess the effects/associations of PA/exercise on the gut microbiome of older adults, to better understand whether physical activity can positively influence the gut microbiome of older adults and whether it can help promote healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
“…The physical performance improved in response to the training, and various measures of physical functions were associated with the abundance of Verrucomicrobia/Akkermansia. Although the training did not affect the alpha-diversity of the GM, the abundances of Phascolarctobacterium and Mitsuokella increased [54].…”
Section: The Effects Of Combined Resistance and Aerobic Exercise On The Gut Microbiotamentioning
confidence: 72%
“…Among these, the top five increasing genera were Pseudobutyrivibrio, Coprococcus_2, Collinsella and Mitsuokella [85]. Mitsuokella has been shown to also increase after eight-weeks of combined aerobic and resistance exercise [54]. The liquid chromatography/mass spectrometry analysis of the fecal metabolites revealed that the levels of 40 metabolites changed in response to the half-marathon [85].…”
Section: The Effects Of Shorter-term Exercise Challenges On the Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation